2008
DOI: 10.1016/j.otohns.2008.05.194
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cochlear Implantation on Vestibular Function

Abstract: Objective-Determine the risk posed by cochlear implantation (CI) to the labyrinth.Study Design-Prospective cohort study. Setting-Academic tertiary referral center.Patients-Thirty-six ears belonging to 35 adult CI candidates (mean: 46, range: 23-69 years old). Intervention-Cochlear implantation.Main Outcome Measures-Vestibular function was assessed using the quantitative 3D head impulse test (qHIT), clinical head impulse test (cHIT), post-headshake nystagmus (HSN), caloric electronystagmography (ENG), vestibula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 32 publications
(49 reference statements)
3
31
0
3
Order By: Relevance
“…In fact, electrode insertion gives rise to a vestibular lesion in the saccule and lateral semicircular canal, so it might be reasonable to evaluate the bithermal caloric response and vestibular evoked myogenic potential in subjects with CI. Although the changes of both test responses were similar in a recent report [Katsiari et al, 2013], most studies reported that the lateral semicircular canal function is much less affected by CI than the saccular function [Krause et al, 2010;Meli et al, 2015;Melvin et al, 2009;Robard et al, 2015]. This was supported by a histopathological study which revealed that the saccule was the most frequently damaged vestibular receptor, followed by the utricle and the semicircular canals [Tien and Linthicum, 2002].…”
Section: Discussionmentioning
confidence: 53%
“…In fact, electrode insertion gives rise to a vestibular lesion in the saccule and lateral semicircular canal, so it might be reasonable to evaluate the bithermal caloric response and vestibular evoked myogenic potential in subjects with CI. Although the changes of both test responses were similar in a recent report [Katsiari et al, 2013], most studies reported that the lateral semicircular canal function is much less affected by CI than the saccular function [Krause et al, 2010;Meli et al, 2015;Melvin et al, 2009;Robard et al, 2015]. This was supported by a histopathological study which revealed that the saccule was the most frequently damaged vestibular receptor, followed by the utricle and the semicircular canals [Tien and Linthicum, 2002].…”
Section: Discussionmentioning
confidence: 53%
“…Some studies have indicated that the sacculus may be particularly susceptible to injury during cochlear implantation Krause et al, 2010;Melvin et al, 2009]. This suggests that specific therapeutic modalities focused on improving responses to linear accelerations might be particularly effective.…”
Section: Mitigation Of Imbalancementioning
confidence: 99%
“…Cochlear implantation can cause damage both to the semicircular canals [Buchman et al, 2004;Enticott et al, 2006;Filipo et al, 2006;Kluenter et al, 2010;Krause et al, 2009Krause et al, , 2010Migliaccio et al, 2005], and the otolith organs Krause et al, 2010;Melvin et al, 2009]. Comparatively few studies have considered the effect of cochlear implantation on postural stability, which is the outcome variable most important to patients [Buchman et al, 2004;Kluenter et al, 2009Kluenter et al, , 2010.…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that this finding depends upon examiner experience, and that experienced examiners are, in fact, less likely to declare a positive sign (refixation saccade) than novice examiners [Jorns-Haderli et al, 2007]. However, when detected, the head thrust sign is a highly specific test of whether or not there has been an ablative lesion on the labyrinth [Minor, 1999;Melvin et al, 2009].…”
Section: Avor Gain Reduction Caloric Reduction and Vertigo Controlmentioning
confidence: 99%